The Effectiveness of the Family Hope Program in Efforts to Control Provety in Bekasi Regency - Yunus, M.; Fardania, Fitri (PERSPEKTIF, 2024)
Indonesia is the country with the fourth largest population in the world. One of the problems faced by the Indonesian people is in organizing the life of society, nation and state. This article aims to analyze the effectiveness of the Family Hope Program and community perceptions of the impact of the Family Hope Program in Karang Satria Village, North Tambun District. This research paradigm uses the constructivism paradigm. The research design is a case study. The research design is a case study. The research method used is qualitative, including observation, in-depth interviews with informants and the community, literature study, and documentation, to measure the effectiveness of the Family Hope Program (PKH) and community perceptions. Assessment indicators include understanding the program, being on target, being on time, achieving goals, and real change. The researcher then developed the determined indicators into interview question items. Data processing and analysis techniques consist of three stages, namely data reduction, data presentation, and concluding. This research concludes that the effectiveness of the Family Hope Program (PKH) for beneficiaries in Karang Satria Village has been able to help reduce the burden of community expenditure, but PKH cannot be said to be completely effective in controlling poverty and increasing income, as seen in this research. from indicators that are right on target and on time. Because PKH only assists individuals who meet the criteria, many rural communities still experience uneven economic growth.